Synthesis of naturally occurring (+)-osmundalactone and 4-epi-(+)-osmundalactone from triacetyl-O-D-glucal - Kotammagari, Tharun K.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Tetrahedron Letters, 2015)
An efficient total synthesis of (+)-osmundalactone 1 has been achieved starting from readily available triacetyl-O-D-glucal 6 employing Ferrier rearrangement and Jones oxidation as key steps. Also, synthesis of 4-epi-(+)-osmundalactone 2 was accomplished from the common key intermediate 9. The absolute stereochemistry of (+)-osmundalactone 1 and a precursor of 4-epi-(+)-osmundalactone 2 have been established by single crystal X-ray analysis. The overall yield of compound 1 and 2 from triacetyl-O-D-glucal 6 is 13% and 8%, respectively. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Bioactive molecules; carbohydrates; D-glucal; Ferrier rearrangement; Pyrones

Synthesis of artemisinin derived glycoconjugates inspired by click chemistry - Goswami, Lakshmi; Paul, Sayantan; Kotammagari, Tharun K.; Bhattacharya, Asish K. (New Journal of Chemistry, 2019)
Herein we describe the synthesis of artemisinin based glycoconjugates (9a-i) through employing a Cu(i)-catalysed reaction between -propargylated dihydroartemisinin (7a) and azido sugars (8a-i), with moderate to excellent yields. Our synthesized artemisinin based glycoconjugates (9a-i) could prove to be an interesting class of bioactive molecules, suitable for the study of their various biological activities.

Synthesis of artemisinic acid derived glycoconjugates and their anticancer studies - Kotammagari, Tharun K.; Paul, Sayantan; Barik, Ganesh K.; Santra, Manas K.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2020)
Glycoconjugates, due to their diverse functions, are widely regarded as biologically important molecules. Artemisinic acid 1 occurs naturally in the plant Artemisia annua and is considered to be the biogenetic precursor of the antimalarial drug, artemisinin 2. We report herein the design and synthesis of diverse artemisinic acid derived glycoconjugates. We have synthesized 12-O-artemisinic acid-glycoconjugates (7a-k) and 12-N-artemisinic acid-glycoconjugates (8a-k) by utilizing Cu(i)-catalyzed azide-alkyne cycloaddition reactions (Click chemistry) with various synthesized sugar azides (6a-k) in good to excellent yields along with two fluorescently labeled compounds, 12-O-artemisinic acid-glycoconjugate 11 and 12-N-artemisinic acid-glycoconjugate 12, to investigate the mode of action of these compounds in biological systems. All the synthesized artemisinic acid glycoconjugates were assayed for their efficacy against the MCF7 cell line. Our anticancer studies indicated that all the synthesized compounds inhibited the growth of MCF7 cells in a dose dependent manner, barring compounds 4 and 7d. However, these compounds exhibit moderate cytotoxicity, as is evident from their IC50 values.